The mandibular gland secretions of the Cape honeybee (Apis mellifera capensis ESCH.) : factors affecting the production of the chemical signal and implications for further development of beekeeping in South Africa - Jones, Georgina Elizabeth (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2001)
The chemical composition of the mandibular gland extracts of Apis mellifera capensis virgin queens was analysed by gas chromatography-mass spectroscopy. Thirty-seven compounds from various chemical groups including aliphatic and aromatic acids and diacids, phenols, alkanes, amino acids and sugars were identified. Among the identified compounds were the queen mandibular pheromone components 9ODA, 9HDA, HVA and HOB and the other aliphatic acids and phenols considered to be the major components of A.m. capensis mandibular glands. Ontogenetic changes in the concentration of the mandibular gland secretions of virgin queens were largely quantitative in nature with the total volume and that of most of the compounds increasing with queen age. The final level of 9ODA is reached at the premating stage, approximately three days after emergence, when it comprises approximately 87% of the major constituents of the mandibular gland signal. Hostile reactions by workers towards introduced virgin queens can be correlated to the relative proportion of 9ODA present in the mandibular gland secretions. This seems to indicate that it is the complete spectrum of the signal and not individual compounds that determine worker reaction towards introduced queens. Keeping queens singly, with or without workers, in an incubator and in small mating nucleus hives proved to be the most successful methods of queen rearing in respect to survival rate in A.m. capensis. The presence of workers during the ageing of virgin queens was found to significantly affect the chemical composition of the mandibular gland secretions of queens. The reaction of workers towards introduced virgin queens reared under different holding conditions varied, with queens reared with workers eliciting significantly less hostile reactions from workers than those reared without workers. Mated queens from five localities in the Eastern Cape were characterised on the basis of the chemical composition of their mandibular gland secretions and the ratio of 9ODA:10HDA. No significant differences were detected and none of the queens sampled could be considered to be A.m. capensis based on their mandibular gland signal. The findings of this study provide baseline data for the development of a queen-rearing program tailored to the specific requirements of A.m. capensis.
Keywords: Honeybee; Honeybee -- Physiology